Caracterização genética, análise do óleo essencial e anatomia foliar de Nectandra megapotamica (Spreng.) Mez. - Costa, Leonardo Severo da (2018)
Nectandra megapotamica (Spreng.) Mez. is a forest species native to Brazil, which presents ecological and pharmacological importance, due to its great potential for the development of new drugs. This aspect has been investigated in recent years by some researchers, mainly in relation to the seasonality of the production of the essential oil of the species, being a great variability in its composition. However, in addition to the effects of seasonality, the genetic characteristics of the species, which together with the abiotic factors determine the composition of the essential oil should be considered. In this sense, the present study had the objective to investigate relevant aspects not yet explored about Nectandra megapotamica (Spreng.) Mez. that contribute to understand the biosynthesis of essential oil in the specie, as well as in congeners. First, the structure and genetic diversity of a natural population were analyzed using RAPD molecular markers. Regarding the analysis of essential oil, the 12 individuals belonging to this population were evaluated in two seasons of the year. Subsequently, to understand the relationship between the genetic diversity of species and essential oil composition, the correlation between these factors was performed. Tests were carried out in the field of microscopy, in which the possibility of using frozen leaf samples was evaluated in the preparation of leaf samples for leaf anatomy analysis was verified. Also, an analysis was performed of the essential oil composition in two seasons. Finally, exploratory experiments were carried out to identify the genes responsible for the synthesis of terpenes, which encode terpene synthases. The RAPD markers allowed to identify that the population is subdivided in three clusters, being verified high levels of genetic diversity within the clusters and high genetic differentiation between them. Due to the great variability observed, both with respect to genetics, evidenced by RAPD markers, and to the essential oil composition, no correlation between these components was verified. Regarding the foliar analysis, it was possible to perform the description, as well as to identify secretory and storage structures. In the additional results, the seasonal analysis of the essential oil composition revealed great variability in oil composition, compared to other studies performed previously with the same individuals. Finally, the tests performed in the field of gene expression, allowed to obtain the partial sequence of a possible gene related to terpene synthases. The set of results obtained could contribute to the continuity of the researches related to Nectandra megapotamica in several areas of knowledge, which had not yet been explored.